Novel advanced scoping meta-review methodology for defining a graduate level textbook in an emerging subject area. - Perry, Simon; McMillan, Norman D.; Rodriguez, Raul D.; Mackowski, Sebastian; Sheremet, Evgeniya; Fleischer, Monika; Kneipp, Katrin; Zahn, Dietrich RT; Adam, Pierre-Michel; Madeira, Teresa Isabel; Meixner, Alfred J. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
This paper describes a library-based project involving the library staff at the Institute of Technology Carlow (ITC), in a collaboration led by the European Cooperation in Science and Technology (COST), Action MP1302 Nanospectroscopy. The project uses a comprehensive scoping methodology, an Advanced Scoping Meta-Review (ASMR), to identify significant topics in an emergent subject area; Optical Nanospectroscopy. An agreed mapping of the subject is derived in order to deliver a pedagogically coherent structure for a three-volume textbook set intended primarily for Early Stage Researchers (ESR). The review process is based on some earlier scoping methodologies, but is devised for a project involving a large number of individuals collaborating in authorship of the textbooks. A description of the scoping process is given, noting both the specific work in searching for and retrieving the appropriate literature, the qualitative and quantitative analysis and ordering of the search results, and placing the meta-review in the wider context of the editorial process to develop the Nanospectroscopy textbooks. The meta-review is employed in a special way in order to map an emergent subject area for the purpose of textbook development, rather than the more traditional use of such reviews to answer specific research questions. The importance of the library-led searching which underpinned this activity is emphasised. The successful outcome of this process resulting in agreement on the detailed content of three volumes is discussed. The paper ends with a critical evaluation of the lessons that can be drawn from this project.